2022
DOI: 10.1161/circresaha.122.321631
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Neuronal Nitric Oxide Synthase Inhibitor on Neurovascular Regulation in Humans

Abstract: BACKGROUND: Neurovascular coupling (NVC) is a key process in cerebral blood flow regulation. NVC ensures adequate brain perfusion to changes in local metabolic demands. Neuronal nitric oxide synthase (nNOS) is suspected to be involved in NVC; however, this has not been tested in humans. Our objective was to investigate the effects of nNOS inhibition on NVC in humans. METHODS: We performed a 3-visit partially randomized, double-blinded, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The systematic literature search yielded 2586 records. After removing 703 duplicates and two retracted papers, we screened 1881 records and finally identified 45 studies that met the eligibility criteria [3, 15–58]. Four additional studies were identified through PubMed and Google Scholar searches and screening relevant articles' reference lists [59–62].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic literature search yielded 2586 records. After removing 703 duplicates and two retracted papers, we screened 1881 records and finally identified 45 studies that met the eligibility criteria [3, 15–58]. Four additional studies were identified through PubMed and Google Scholar searches and screening relevant articles' reference lists [59–62].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of the 49 eligible studies had been conducted in awake healthy subjects [15, 17, 18, 20, 30–32, 37, 39–41, 46, 47, 53, 58] and the remaining 34 studies in anaesthetised subjects [3, 16, 19, 21–29, 33–36, 38, 42–45, 48–52, 54–57, 59–62]. Among the latter, 31 involved patients undergoing various surgical procedures [3, 16, 19, 21–23, 25–29, 34–36, 38, 42–45, 48–52, 54, 55, 57, 59–62], two involved healthy volunteers [24, 33] and one involved patients with hyperdynamic sepsis or cardiac diseases [56].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations